(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aims to examine the effect of positioning strategy on consumer perception at Hanoon Industries, with brand engagement as a moderating variable. The research employs a quantitative descriptive and associative approach with a sample of 100 respondents. Data were analyzed using simple linear regression and moderated regression analysis through SPSS. The results indicate that positioning strategy has a positive and significant effect on consumer perception. Furthermore, brand engagement is proven to moderate and strengthen the relationship between positioning strategy and consumer perception. These findings highlight the importance of integrating effective positioning strategies with strong consumer engagement to build positive brand perceptions in the local fashion industry.